1992
DOI: 10.1213/00000539-199204000-00008
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and Pharmacodynamics of Vecuronium in the Obese Surgical Patient

Abstract: The effect of obesity on the disposition and action of vecuronium was studied in 14 surgical patients. After induction of anesthesia with thiopental and maintenance of anesthesia by inhalation of nitrous oxide and halothane, seven obese patients (93.4 +/- 13.9 kg, 166% +/- 30% of ideal body weight, mean +/- SD) and seven control patients (60.9 +/- 12.3 kg, 93% +/- 6% of ideal body weight) received 0.1 mg/kg of vecuronium. Plasma arterial concentrations of muscle relaxant were determined at 1, 3, 5, 10, 15, 20,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(44 citation statements)
references
References 3 publications
1
42
0
1
Order By: Relevance
“…In the same study, the authors also observed that although atracurium concentrations were higher in the obese than nonobese patients, there was no difference between the 2 groups in the time of recovery from neuromuscular blockade. Schwartz et al [91] evaluated the pharmacokinetic and pharmacodynamic profiles of vecuronium administered to 7 obese and 7 normal-weight subjects and showed that when the data were calculated on the basis of IBW, total volume of distribution (791 F 303 vs 919 F 360 mL/kg), plasma clearance [4.65 zF 0.89 vs 5.02 F 1.13 mL/(mind kg)], and elimination half-life (119 F 43 vs 133 F 57 minutes) did not differ between obese and nonobese patients. Nonetheless, the authors reported a difference in duration of action of vecuronium in obese patients compared with nonobese subjects.…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…In the same study, the authors also observed that although atracurium concentrations were higher in the obese than nonobese patients, there was no difference between the 2 groups in the time of recovery from neuromuscular blockade. Schwartz et al [91] evaluated the pharmacokinetic and pharmacodynamic profiles of vecuronium administered to 7 obese and 7 normal-weight subjects and showed that when the data were calculated on the basis of IBW, total volume of distribution (791 F 303 vs 919 F 360 mL/kg), plasma clearance [4.65 zF 0.89 vs 5.02 F 1.13 mL/(mind kg)], and elimination half-life (119 F 43 vs 133 F 57 minutes) did not differ between obese and nonobese patients. Nonetheless, the authors reported a difference in duration of action of vecuronium in obese patients compared with nonobese subjects.…”
Section: Muscle Relaxantsmentioning
confidence: 99%
“…In obese patients, the speed of onset was expected to be faster because of a smaller distribution volume per body weight [14]. The multiple regression analysis in this study demonstrated that this prediction was correct, [8], and the priming technique.…”
Section: Discussionmentioning
confidence: 72%
“…AE Schwartz, et al 22 proved that time to recovery from neuromuscular blockade was longer in obese patients (93.4 + 13.9 kg) as opposed to non-obese patients (60.9 + 12.3 kg).Cynthia A Lien, et al 23 and De Almeida Mc, et al 24 concluded that an anesthetist should expect the action of vecuronium to be prolonged in elderly surgical patients. The altered pharmacokinetics and age related changes in renal and hepatic function prolonged the recovery time.…”
Section: Discussionmentioning
confidence: 99%